Identification of murine nuclear proteins that bind to the conserved octamer sequence of the immunoglobulin promoter region. - Hanke, J H (1988)
Sequence-specific DNA-affinity chromatography was used to purify a nuclear protein from the B-cell leukemia cell line BCL1 that specifically binds to the octamer sequence ATTTGCAT, previously shown to be important in the regulation of immunoglobulin genes. This protein has a molecular mass of approximately 70 kDa and is responsible for the protein-DNA interaction specific to lymphoid cells. Other proteins of molecular mass 80-90 kDa and 50-55 kDa that specifically bind to the octamer sequence were also identified. These results demonstrate that the octamer is recognized by several biochemically distinct nuclear proteins, perhaps to differentially regulate the expression of immunoglobulin genes.